2023
DOI: 10.1186/s41182-023-00509-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and hesitancy to receive COVID-19 vaccine among university students in Egypt: a nationwide survey

Abstract: Background The public's willingness to be vaccinated will determine the success of the COVID-19 vaccination program. The aim of this study was to identify acceptance and hesitancy to receive COVID-19 vaccine among university students in Egypt, assess their level of knowledge about COVID-19 vaccine and identify factors that influence their intention towards COVID-19 vaccination. Methods A standardized and self-administered questionnaire was distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Compared with the unvaccinated group, a significantly larger proportion of the vaccinated group thought vaccines could provide protection (77.4 vs. 84.2%). The rates are in parallel with those of the general population ( 29 , 41 ). Over half of the participants got vaccinated because of “fear of infection,” and nearly 10% of the vaccinated participants did not want to receive the next dose because they believed the current vaccine was enough to provide protection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with the unvaccinated group, a significantly larger proportion of the vaccinated group thought vaccines could provide protection (77.4 vs. 84.2%). The rates are in parallel with those of the general population ( 29 , 41 ). Over half of the participants got vaccinated because of “fear of infection,” and nearly 10% of the vaccinated participants did not want to receive the next dose because they believed the current vaccine was enough to provide protection.…”
Section: Discussionmentioning
confidence: 94%
“…According to a survey study in Poland, 49.2% of the participants refused to receive a booster dose because of side effects experienced after previous doses, and 22.4% because of safety uncertainties ( 28 ). In addition, a recent study among university students in Egypt revealed that the main reason for vaccine hesitation was being afraid of serious side effects ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in the literature show that lower levels of education is associated with lower acceptance. They may also be more influenced by misinformation spread by social media and by parental attitudes against vaccines [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The perception of the vaccine's adverse effects is the most common reason for participants' refusal to take it. The risk of side effects is the main barriers for vaccinations in other countries also 19 . People utilized a variety of information resources to learn about the COVID-19 pandemic, including mass media (radio, television, newspapers), friends, social media, healthcare practitioners, coworkers, researchers, governments, and so on 20 .…”
Section: Figure Iii: Sources Of Getting Vaccine Related Informationmentioning
confidence: 99%